3D Winding Number: Theory and Application to Medical Imaging - Alessandro Becciu; Andrea Fuster; Mark Pottek; Bart van den Heuvel; Bart ter Haar Romeny; Hans van Assen (International Journal of Biomedical Imaging)
We develop a new formulation, mathematically elegant, to detect critical points of 3D scalar images. It is based on a topological number, which is the generalization to three dimensions of the 2D winding number. We illustrate our method by considering three different biomedical applications, namely, detection and counting of ovarian follicles and neuronal cells and estimation of cardiac motion from tagged MR images. Qualitative and quantitative evaluation emphasizes the reliability of the results.